Sustained Complete Response to Metronomic Chemotherapy in a Child with Refractory Atypical Teratoid Rhabdoid Tumor: A Case Report - Berland, Mahe; Padovani, Laetitia; Rome, Angélique; Pech-Gourg, Grégoire; Figarella-Branger, Dominique; André, Nicolas (Frontiers in Pharmacology, 2017)
Atypical teratoid rhabdoid tumor (ATRT) is a rare and highly aggressive embryonal tumor of the central nervous system with a dismal prognosis and no definitive guidelines for treatment, especially at relapse or in case of refractory disease. Metronomic chemotherapy (MC) has emerged as a new treatment option in solid malignancies, with lower toxicity and is frequently combined with drug repositioning. We report a case of ATRT in an 8-year-old boy who progressed during multimodal therapy including surgical resection, chemotherapy and radiotherapy. He was treated with MC involving continuous oral celecoxib with alternating metronomic etoposide and cyclophosphamide, in combination with biweekly bevacizumab and monthly intrathecal liposomal cytarabine. To date, he remains clinically and symptomatically disease-free with a follow-up of 10 months. The treatment was well tolerated. Metronomics represent a possible alternative regimen for children with recurrent or progressive ATRT.